2010
DOI: 10.1111/j.1365-2915.2010.00923.x
|View full text |Cite|
|
Sign up to set email alerts
|

Novel field assays and the comparative repellency of BioUD®, DEET and permethrin against Amblyomma americanum

Abstract: Two new field bioassay methods were developed to compare the repellent activity of BioUD(®) (containing 7.75% 2-undecanone), 98.1% DEET and 0.5% permethrin against natural populations of nymphal Amblyomma americanum (L.) (Acari: Ixodidae). In a cloth sheet assay, pieces of material measuring 41 × 58 cm, separately treated with one of the test materials or the appropriate solvent carrier, were placed at random on the ground and baited with dry ice for 1 h. Mean numbers of ticks on repellent-treated sheets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The ideal would be to have a laboratory assay system that would be a certain mimic of uses in the field. Bissinger et al [41] for example, found an excellent correlation between tick Petri dish repellency assays and human subject tests in the field for two commercial products, DEET and BioUD. They concluded, at least for these two products that the laboratory assay was an acceptable predictor of their practical use in the field.…”
Section: Bioassay Methods For Acarine Attractantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal would be to have a laboratory assay system that would be a certain mimic of uses in the field. Bissinger et al [41] for example, found an excellent correlation between tick Petri dish repellency assays and human subject tests in the field for two commercial products, DEET and BioUD. They concluded, at least for these two products that the laboratory assay was an acceptable predictor of their practical use in the field.…”
Section: Bioassay Methods For Acarine Attractantsmentioning
confidence: 99%
“…This basic design can easily determine if a chemical can function as an attractant in field applications. By examining capture rates over time, information is obtained about the duration of attractant activity [41,42]. While on the surface, such an assay may seem simple to conduct, the placement of treatments and controls can be problematic because acarine populations are not always evenly distributed in the landscape.…”
Section: Bioassay Methods For Acarine Attractantsmentioning
confidence: 99%
“…The evidence for repellent useÑ one of the most commonly promoted methods of personal protection against tick bitesÑto lower the risk of B. burgdorferi infection is limited (Klein et al 1996, Smith et al 2001, Vazquez et al 2008, Connally et al 2009, Bissinger et al 2011. There is no question that I. scapularis is repelled from skin and clothing by commercially available repellents containing DEET and other active ingredients (Carroll et al 2004, Environmental Protection Agency 2010.…”
Section: How Does Human Behavior Influence Lyme Disease Risk and Whatmentioning
confidence: 96%
“…The ticks were prevented from entering the mixing chamber by metal mesh on the upwind end of the olfactometers. All airflow rates were 50 mL/min (Bissinger et al, 2011) and verified between each assay using a mass flow meter (AALBORG ® GFM 171, Orangeburg, NY). Humidity in the air flow was routinely measured at the stem of the olfactometer using a data logger with an external probe sensor (U14-002, HOBO, Onset Computer Corporation, Bourne, MA).…”
Section: Olfactometer Assaysmentioning
confidence: 99%